Gauge Covariance of the Gap Equation: From the Rainbow Truncation to Gauge Symmetry Constraints - El-Bennich, Bruno [UNESP] (MDPI, 2025)
The gauge covariance of the quark gap equation is compared for the case of three different quark–gluon vertices: the bare vertex, a Ball–Chiu-like vertex constrained by the corresponding Slavnov–Taylor identity, and a full vertex including the transverse components derived from transverse Slavnov–Taylor identities. The covariance properties are verified with the chiral quark condensate and the pion decay constant in the chiral limit.
Keywords: dynamical chiral symmetry breaking; Dyson–Schwinger equation; gap equation; gauge covariance; light quarks; quantum chromodynamics